VARIABILITAS FENOTIPIK TANAMAN GAMBIR DI DESA TANJUNG, KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - SEPRITA LIDAR; ENNY MUTRYARNY; TRISIA WULANTIKA (Jurnal Ilmiah Pertanian, 2018)
ABSTRACT Gambier is one commodity that is worth people's plantation economy and prospective for higher developed commercially in the future. Riau Province gambir Subdistrict where producers including the Gambier plantation had the most extensive is a subdistrict of Koto Kampar Kampar Regency acres 4,104 Upstream Research entitled "analysis ofthe Phenotypic variability of Gambir Plant in the village of Tanjung, Kec. Koto Kampar, Kampar Regency of Hulu "has been conducted in March - April 2018, research method using the method of purposive sampling, the samples taken 30 accession later analysis of similarity using the ntsys program ver 2.02. Obtained Results narrow Variability on all character observations. Similarity coefficient gambir accessions ranged from 0.33-0.93. Keywords: Gambir, Variability ,Germplasm, Phenotypic Characterization